Pengaruh tekanan eksternal, komitmen manajemen dan aksesibilitas terhadap transparansi pelaporan keuangan - Rahim, Serlyna; Suwandi, Suwandi (ARKA INSTITUTE, 2022)
This study aims to determine the effect of external pressure, management commitment and accessibility on transparency of financial reporting. In this study, researchers examined the transparency of financial reporting in Regional Apparatus Organizations (OPD) of Gresik Regency using independent variables, namely external pressure, management commitment and accessibility. Sampling was carried out using the purposive sampling method and the number of samples was 25 OPDs. The primary data collection method used was the questionnaire method with several predetermined criteria. The media used for data collection was by sending via Google from those who had previously requested permission and assistance from each related OPD to distribute research questionnaires to employees who carry out administration in OPDs who were considered to meet certain criteria. The data analysis technique used in this study was SEMPLS. The results of hypothesis testing in this study indicate that external pressure and accessibility have an effect on transparency of financial reporting. It can be concluded that the better the access given to stakeholders to access regional financial information, the better the transparency of the regional government's financial reporting.